Analysis of the early cellular and humoral responses of Galleria mellonella larvae to infection by Candida albicans. Issue 1 (31st December 2018) - Sheehan, Gerard; Kavanagh, Kevin
ABSTRACT: Galleria mellonella larvae were administered an inoculum of Candida albicans and the response to infection over 24 hours was monitored. The yeast cell density in infected larvae declined initially but replication commenced six hours post-infection. The hemocyte density decreased from 5.2 × 10 6 /ml to 2.5 × 10 6 /ml at 2 hours but increased to 4.2 × 106 at 6 hours and decreased subsequently. Administration of β – glucan to larvae also caused a fluctuation in hemocyte density (5.1 ± 0.22 × 10 6 /ml (0 hour) to 6.25 ± 0.25 × 106/ml (6 hour) (p < 0.05) to 5 ± 2.7 × 106 (24 hour)) and the population showed an increase in the density of small, granular cells at 24 hours (p < 0.05). Hemocytes from larvae inoculated with β – glucan for 6 or 24 hours showed faster killing of C. albicans cells (53 ± 4.1% (p < 0.01), 64 ± 3.7%, (p < 0.01), respectively) than hemocytes from control larvae (24 ± 11%) at 60 min. Proteomic analysis indicated increased abundance of immune related proteins cecropin-A (5 fold) and prophenoloxidase-activating proteinase-1 (5 fold) 6 hours post infection but by 24 hours there was elevated abundance of muscle (tropomyosin 2 (141 fold), calponin (66 fold), troponin I (62 fold)) and proteins indicative of cellular stress (glutathione-S-transferase-like protein (114 fold)), fungal dissemination (muscle protein 20-like protein (174 fold)) and tissue breakdown (mitochondrial cytochrome c (10 fold)). Proteins decreased in abundance at 24 hour included β – 1, 3 – glucan recognition protein precursor (29 fold) and prophenoloxidase subunit 2 (25 fold).